Uptake of dietary amino acids into arterial blood during continuous enteral feeding in critically ill patients and healthy subjects. Issue 3 (March 2021) - Liebau, Felix; Király, Emilie; Olsson, Daniel; Wernerman, Jan; Rooyackers, Olav
Summary: Background: Amino acid availability is a regulatory factor of protein anabolism and is partly dependent on enteral amino acid uptake. During continuous enteral feeding, enteral amino acid uptake may vary considerably, but this has not been documented systematically. Methods: In this pragmatic study, we investigated patients in the intensive care unit (n = 10) and healthy adults (n = 10). The time course of essential amino acid concentrations in arterial plasma and the uptake of dietary phenylalanine were recorded during 12 hours of continuous enteral feeding, using a 13 C-labeled phenylalanine tracer. Results: Plasma essential amino acid concentrations and 13 C-phenylalanine enrichment reached a tentative steady state after no more than 4.5 h from start of tracer infusion. There was a large intra- and inter-individual variability in both cohorts. No periodicity could be detected in the temporal variation. Conclusion: During continuous enteral feeding, uptake of amino acids shows large intra- and inter-individual variation. A tentative steady state of 13 C-phenylalanine uptake is eventually reached. Trial registration: Registered at Australian New Zealand Clinical Trials Registry, trial ID ACTRN12616000593437.